Efficacy comparison of titrated oral solution of misoprostol and intravenous oxytocin on labour induction in women with full-term pregnancy. (2nd January 2020) - Kashanian, Maryam; Eshraghi, Noushin; Rahimi, Maryam; Sheikhansari, Narges; Javanmanesh, Forough
Abstract: A double-blind randomised trial was conducted on women with gestational age of 40–42 weeks of pregnancy and Bishop score of more than 5. The first group received oxytocin infusion and the second group received a titrated oral solution of misoprostol. Then, the two groups were compared by the primary outcome (the number of deliveries in the first 24 hours of intervention). The two groups did not have any significant difference in maternal and gestational age at the time of intervention, primary Bishop score, parity and neonatal weight. The number of deliveries in the first 24 hours was greater in the misoprostol group. Duration of onset of intervention to proper contractions was longer in the misoprostol group. However, the number of deliveries between 6–12 hours, 12–18 hours and 18–24 hours after induction was greater in the misoprostol group. The incidence of tachysystole and meconium was greater in the misoprostol group. Impact statement: What is already known on this subject? Labour induction is widely used where the continuation of pregnancy might be dangerous for the mother or the baby. Of the various methods used for induction, misoprostol which is a prostaglandin E1 analogue has been reviewed more in recent years. Misoprostol has various routes of administration but in most studies only vaginal administration has been evaluated, leaving us with limited data about oral administration. What do the results of this study add? Oral misoprostol is a suitable method for labour induction and can be used as an alternative to oxytocin. What are the implications of these findings for clinical practice and/or further research? Misoprostol is not expensive, has a long shelf life, accessible in underdeveloped countries and rural areas and has several routes of administrations such as oral, sublingual and vaginal. Despite the fact that the oral route of misoprostol has a fast absorption and easier administration, there are relatively few studies assessing the the use of the oral route of misoprostol. Misoprostol is a suitable method for Labour induction and it has the potentials of being used as an alternative for oxytocin, however, the optimum dosages, the preferred route of administration, the maximum dose, the maximum time for administration, and maternal and neonatal safety should be studied more.